Analisa Kinerja Simpang Bersinyal (Studi Kasus : Persimpangan Jalan Delima – Jalan Lobak – Jalan Srikandi – Jalan Melati Indah) - Rachmat Al Izzan; Sri Djuniati; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Delima intersection is a 2/2 four arms UnDivided crossing. The environment around this intersection is a commercial area. There are several activities at the intersection approach, such as vehicles in and out of the shopping area intersections theat cause congestion. The purpose of this study is to analyze the performance of Delima intersections and to find out the level of road service. The method used in this study was Indonesian Higway Capacity Manual 1997 which includes analysis of intersection capacity, queue length, signalised phase and delay. Data were obtained by conducting a survey of traffic flow conditions, cycle time and geometric intersection. From the results, the analysis of signalised performance on the existing condition of the highest delay is the North approach with an average delay value of 310.95 sec/smp and the level of service is included in category D. This is necessary to do alternative intersection settings. From the three alternatives considered, the alternative three is the best alternative with the delay value generated in the afternoon peak hours is 6.03 sec/smp. The level of service in all three alternative peak hours is included in category B. Keywords: Signalised Intersections, Delays, Level of Service, Cycle Time